Особливості локальних теплових процесів у регіоні Дніпровсько-Донецької западини - Лубков, М.В. (Геоінформатика, 2016)
З метою дослідження аномальних локальних теплових процесів у регіоні Дніпровсько-Донецької западини (ДДЗ) на основі варіаційної скінченно-елементної методики для нестаціонарної задачі теплопровідності змодельовано локальні приповерхневі теплові процеси у зоні сучасної активізації ДДЗ. Показано, що процеси нагріву приповерхневих зон осадових порід земної кори в околах аномальних температурних джерел ДДЗ, які зумовлені переміщенням гарячих флюїдів по активізованих розломах, суттєво залежать від етапу розігріву і наявності у навколишніх зонах високотеплопровідних соляних масивів. У випадку нестабільності аномальних температурних джерел за часом загальна картина розвитку локальних теплових полів визначатиметься періодами їх відносної активності. За розташуванням локальних теплових полів на земній поверхні та їх кількісними характеристиками (поверхневий тепловий потік, температурні градієнти) можна локалізувати місця активізованих глибинних розломів та пов’язані з ними процеси накопичення вуглеводневої сировини в регіоні ДДЗ. С целью исследования аномальных локальных тепловых процессов в регионе Днепровско-Донецкой впадины (ДДВ) на основе вариационной конечно-элементной методики для нестационарной задачи теплопроводности проведено моделирование локальных приповерхностных тепловых процессов в зоне современной активизации ДДВ. Показано, что процессы нагрева приповерхностных областей осадочных пород земной коры в окрестностях аномальных температурных источников ДДВ, вызванных перемещениями горячих флюидов по активизированным разломам, существенно зависят от этапа разогрева и наличия в окружающих областях высокотеплопроводных соляных массивов. В случае нестабильности аномальных температурных источников во времени общая картина развития локальных тепловых полей будет определяться периодами их относительной активности. По расположению локальных тепловых полей на земной поверхности и их количественным характеристикам (поверхностный тепловой поток, температурные градиенты) можно локализовать места активизированных глубинных разломов и связанные с ними процессы накопления углеводородного сырья в регионе ДДВ. Purpose. The Dnepr-Donetsk Depression (DDD) is part of the Dnepr-Donetsk rift located in the northern east of the Ukrainian part of the Eastern European lithospheric plate, DDD is a system of deep faults, which stretch from southern- east to northern west and form a band of blocks and microblocks of crystalline fundament falling down along the faults. According to the recent geophysical and geological data, the central, southern-east and partially southern-west parts of DDD during the last 3—5 ml years have been under action of modern geotectonic activity. These processes become apparent through tectonic activity of longitudinal and transversal DDD faults, and also due to circulation in the near surface crust layers of deep high push hot fluids. For better understanding of modern geotectonic processes which take place in DDD region, as well as concurring processes of generation, migration and accumulation of hydrocarbon stuff, it is very important to investigate the local geothermal regimes that control the wide circle of physical-chemical and geodynamical processes. Design/methodology/approach. On the basis of the variation finite element method for the non-stationary heat conductivity problem, we carried out modeling of the local near earth surface heat processes in the modern activity zone of DDD. Findings. The results of computer modeling of the local near earth surface heat processes in the modern activity zone of DDD show that heating processes of the sedimentary regions near abnormal temperature sources, caused by displacements of hot fluids in the active faults, essentially depend on the heating stage and presence of surrounding high conductivity salt masses. In the case of abnormal temperature sources instability, the total picture of the local heat field development is to be defined based on their relative activity periods. So the character of the earth surface local heat fields’ location and their quantitative characteristics (surface heat flux value, temperature gradients) permit to localize places of active deep faults and concurring processes of hydrocarbon stuff accumulation in the DDD region. Practical value/implications. The obtained results can be used for practical geologic works to find sites of hydrocarbon stuff accumulation in the DDD region. For further studies, it would be interesting to use the presented method for more detailed investigation of specific oil-gas deposits structures in this region.